The relationship between reinforcement sensitivity and non-suicidal self-injury among adolescents: moderated mediation effect - Kong, Rong; Chen, Ruihua; Hou, Tingyu; Li, Na (Frontiers in Psychology, 2025)
ObjectiveNon-suicidal self-injury (hereinafter referred to as NSSI) is a significant public health concern among adolescents. Understanding its underlying psychological mechanisms is crucial for developing effective interventions. This study explored how reinforcement sensitivity affects NSSI among adolescents in China.MethodsA moderated mediation effect model was constructed to investigate the mediating role of self-criticism in the relationship between reinforcement sensitivity and NSSI, as well as the moderating role of self-compassion in this mediated pathway. A questionnaire survey was conducted with 1,582 middle school students. The study utilized established scales, including the BIS/BAS Scale, the Self-Criticism scale, the Self-Compassion Scale and the Adolescents Self-Harm Scale.ResultsA total of 1,448 valid questionnaires were analyzed. The results showed that (1) punishment sensitivity can significantly positively predict NSSI among adolescents, with self-criticism partially mediating this relationship; (2) fun-seeking can significantly positively predict NSSI among adolescents, with self-criticism fully mediating this relationship; (3) reward responsiveness can significantly negatively predict NSSI among adolescents, with self-criticism partially mediating this relationship; (4) the relationship between self-criticism and NSSI was moderated by self-compassion (the latter half of the mediation effect).ConclusionThese results not only enhance our understanding of the mechanisms and conditions under which reinforcement sensitivity impacts adolescents’ NSSI, but also have important implications for targeted intervention measures.